Assessing the construct validity of a theory of mind battery adapted to Tunisian school-aged children - Salhi, Imène Soumaya; Lancelot, Céline; Marzouki, Yousri; Souissi, Wided; Besbes, Aya Nejiba; Le Gall, Didier; Bellaj, Tarek (Frontiers in Psychiatry, 2023)
Background: The Theory of Mind (ToM) refers to the ability to understand others’ states of mind, desires, emotions, beliefs, and intentions to predict the content of their mental representations. Two major dimensions within the ToM have been studied. The first refers to the type of inferred mental state that can be cognitive or affective. The second refers to the types of involved processes according to their degree of complexity (ﬁrst and second-order false-belief, and advanced ToM). The acquisition of ToM is a fundamental key component for the development of everyday human social interactions. ToM deficits were reported in different neurodevelopmental disorders through various tools assessing different facets of social cognition. In this regard, Tunisian practitioners and researchers do not have any linguistically and culturally appropriate psychometric tool for the assessment of ToM in school-aged children. Objective: To assess the construct validity of a translated and adapted French ToM Battery for Arabic-speaking Tunisian school-aged children. Method: This ToM Battery was designed based on neuropsychological and neurodevelopmental theoretical frameworks. It was composed of 10 subtests distributed evenly in three parts: Preconceptual, cognitive, and affective ToM. The ToM battery was administered individually after being translated and adapted to the Tunisian socio-cultural context to 179 neurotypical Tunisian children (90 girls and 89 boys) aged from 7 to 12 years. Results: After controlling for the age effect, the evidence of construct validity based on two dimensions (i.e., cognitive and affective) was confirmed by the SEM analysis that showed the presence of a two-component model with a good fit. Findings confirmed afterward that the age affected differentially the performance obtained on ToM tasks based on the two components of the battery. Conclusion: These findings confirm that the Tunisian version of the ToM Battery has a robust construct validity for the assessment of cognitive and affective ToM in Tunisian school-aged children and could be used in clinical and research settings.